Welfare state survey 1997 - Edlund, Jonas; Svallfors, Stefan (Umeå University, 2003)
This survey, inquiring the Swedish people's attitudes towards the public sector and the taxes, is a follow-up of two earlier surveys conducted in 1986 and 1992. A number of questions are also similar to those put in the 1996 ISSP-survey. In the survey respondents had to give their opinion on public expences and social services: if they wanted the amount of tax money spent on a number of different areas to increase, decrease or to be kept unchanged; how to finance education, medical service, child care and care of the elderly; and best suited to take care of education, medical service, child care, care of elderly, and social welfare. Furthermore, the respondents had to state how to distribute the responsibility for financing social insurances between the individual and the public sector; how common they believe it to be that social security benefits and social care services are misused; and how well the public sector manage to maintain different services. Respondents also had to report their own as well as their family´s and friends´ experiences of social services during the last three years. Other questions dealt with the probability of being unemployed; not getting the medical care you need; not managing a month of sick leave without serious economical consequences; not affording to pay a visit to the doctor; having to move because of high housing costs; having a state pension that would not give an acceptable living standard. Respondents also had to state if they felt a need for private insurances to supplement the public welfare system. A number of questions dealt with opinions on Swedish taxes: willingness to pay more tax if the money was spent on specific areas such as medical care, support for elderly, support for families with children, social allowance, schooling, and measures for generating employment; the pressure of taxation in general, and for various income brackets; and the respondents´ judgement on total taxation for recipients of high, middle and low incomes. For a number of statements occurring in the current Swedish debate the respondents had to state if they agreed or not. Socio-economic background information include occupation, trade union affiliation, education, income, marital status, spouse´s occupation, household income, number of children, and political preference.

Denna undersökning är en uppföljning av två tidigare undersökningar genomförda 1986 och 1992. Ett antal av undersökningens frågor återfinns också i 1996 års ISSP-undersökning. Respondenterna fick för ett antal påståenden, hämtade från den aktuella svenska debatten, ange om man instämde eller ej. Därutöver fick man ange sin inställning till, och erfarenhet av, offentliga utgifter och social service, hur man anser olika verksamheter ska finansieras och vilka som är bäst lämpade att sköta olika verksamheter. Ett antal frågor berör socialförsäkringar och hur ansvaret bör fördelas mellan den enskilde och det offentliga när det gäller att betala dessa försäkringar. Respondenterna fick även ange hur vanligt man tror det är att sociala bidrag och tjänster missbrukas och vilka egna erfarenheter man haft av social service. En serie frågor berörde sannolikheten för att man själv kommer att råka ut för en situation där privatekonomin kommer att påverkas negativt, och om man känner ett behov av att komplettera det offentliga välfärdssystemet med egna privata försäkringar. En serie frågor behandlade åsikter om de svenska skatterna, skattetrycket allmänt och för olika inkomstgrupper, samt inställning till att inte uppge alla inkomster och därigenom betala mindre i inkomstskatt. Socio-ekonomiska bakgrundsuppgifter inkluderar sysselsättning, facklig organisationstillhörighet, utbildning, politisk preferens, bostad, inkomst, civilstånd, makes/sambos sysselsättning och inkomst, antal barn i hushållet, samt föräldrars medborgarskap.
Välfärdsstatsundersökningen 1997
Åsikter om den offentliga sektorn och skatterna 1997
Keywords: PUBLIC SECTOR; OFFENTLIG SEKTOR; CARE OF THE ELDERLY; ÄLDREOMSORG; FISCAL POLICY; SKATTEPOLITIK; SOCIAL WELFARE; SOCIAL VÄLFÄRD; PUBLIC EXPENDITURE; OFFENTLIG UTGIFT; SOCIAL WELFARE EXPENDITURE; UTGIFT FÖR SOCIAL VÄLFÄRD; EDUCATIONAL EXPENDITURE; UTBILDNINGSUTGIFT; CHILD CARE; BARNOMSORG; MEDICAL CARE; SJUKVÅRD; PUBLIC SERVICES; OFFENTLIG SERVICE; PRIVATIZATION; PRIVATISERING; TAXATION; BESKATTNING; SOCIAL SECURITY BENEFITS; SOCIALFÖRSÄKRINGSFÖRMÅNER; EDUCATION; UTBILDNING; SOCIAL WELFARE FINANCE; FINANSIERING AV SOCIAL VÄLFÄRD; WELFARE ECONOMICS; VÄLFÄRDSEKONOMI; SOCIAL WELFARE PHILOSOPHY; SOCIAL VÄLFÄRDSFILOSOFI; TAX EVASION; SKATTEFLYKT; Economic policy, public expenditure and revenue; Ekonomisk politik, offentliga utgifter och intäkter; Social welfare policy; Välfärdspolitik; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi